Brain insulin resistance impairs hippocampal synaptic plasticity and memory by increasing GluA1 palmitoylation through FoxO3a. Issue 1 (December 2017) - Spinelli, Matteo; Fusco, Salvatore; Mainardi, Marco; Scala, Federico; Natale, Francesca; Lapenta, Rosita; Mattera, Andrea; Rinaudo, Marco; Li Puma, Domenica; Ripoli, Cristian; Grassi, Alfonso; D'Ascenzo, Marcello; et al.
Abstract High-fat diet (HFD) and metabolic diseases cause detrimental effects on hippocampal synaptic plasticity, learning, and memory through molecular mechanisms still poorly understood. Here, we demonstrate that HFD increases palmitic acid deposition in the hippocampus and induces hippocampal insulin resistance leading to FoxO3a-mediated overexpression of the palmitoyltransferase zDHHC3. The excess of palmitic acid along with higher zDHHC3 levels causes hyper-palmitoylation of AMPA glutamate receptor subunit GluA1, hindering its activity-dependent trafficking to the plasma membrane. Accordingly, AMPAR current amplitudes and, more importantly, their potentiation underlying synaptic plasticity were inhibited, as well as hippocampal-dependent memory. Hippocampus-specific silencing of Zdhhc3 and, interestingly enough, intranasal injection of the palmitoyltransferase inhibitor, 2-bromopalmitate, counteract GluA1 hyper-palmitoylation and restore synaptic plasticity and memory in HFD mice. Our data reveal a key role of FoxO3a/Zdhhc3/GluA1 axis in the HFD-dependent impairment of cognitive function and identify a novel mechanism underlying the cross talk between metabolic and cognitive disorders. Metabolic diseases have been associated with cognitive impairment. Here, the authors show that brain insulin resistance induced by high-fat diet leads to increased palmitoylation of AMPA receptors and thus changes in hippocampal plasticity, learning and memory.